Photorespiratory changes and induced resistance on tomato against septoria leaf spot by a phosphite combined with free amino acids - Silva, Bruno do Nascimento (2022)
Septoria leaf spot (SLS), caused by Septoria lycopersici, is a destructive disease in tomato. Infection of plants by pathogens causes changes in photosynthesis, photorespiration and respiration that will affect defense responses. The first study investigated the impacts caused on photorespiration in tomato leaves by S. lycopersici infection. Infection reduced photosynthesis and pigment concentration and increased respiration and the photorespiration/crude photosynthesis ratio increased in infected leaves. S. lycopersici infection caused great oxidative damage as demonstrated by increased concentrations of malonaldehyde, superoxide anion and hydrogen peroxide. We evaluated the expression of genes involved in the photorespiratory pathway (GOX1, GOX2, SHMT2, SMHT3 and GLYK), nitrogen metabolism (Fd-GOGAT) and stress acclimatization (mMDH1, mMDH2 and CAT) and observed an up- regulation during the process of S. lycopersici infection. A better understanding of the physiological changes that occur in the leaves of tomato plants infected by S. lycopersici at the level of photorespiration may contribute to the development of cultivars more efficiently to cope with the fungal infection. In the second study, we investigated the use of potassium phosphite combined with free L-α-amino acids (called stimulus induced resistance (IR)) to increase tomato defense responses against S. lycopersici infection. Plants that received the RI stimulus showed a reduction in the severity of SLS and less colonization of leaf tissue by S. lycopersici (lower expression of TEF-1α). Plants sprayed with IR stimulus showed lower concentrations of malonaldehyde, hydrogen peroxide and superoxide anion radical, while sucrose, fructose and starch concentrations and high ascorbate peroxidase, catalase, glutathione reductase and superoxide dismutase activities increased when compared to plants sprayed with IR stimulus. water in response to S. lycopersici infection. The photosynthetic apparatus was less compromised, which resulted in higher concentrations of chlorophyll a+b and carotenoids in plants sprayed with RI stimulus. We observed that genes involved in host defense reactions (CHI3, CHI9, GLU, PAL3, POX3, PPOB and PPOF) and those related to acquired systemic resistance (PAL3 and ICS) or induced systemic resistance ((ethylene production - ACO2, ACO3, ACO5 and ACO4) and the jasmonic acid signaling pathway (LOX1.1, LOXB, LOXC andPDF1.2)) and we observed an up-regulation for plants infected and sprayed with RI stimulus. These findings highlight the potential of using this IR stimulus for the management of SLS. Keywords: Antioxidative metabolism. Foliar disease. Host defense responses. Induced resistance. Necrotrophic pathogen.